The biotribological behaviour researches on the α-tocopherol-doped and gamma-irradiated UHMWPE. (17th May 2010) - Ni, Zifeng; Ge, Shirong
The effect of antioxidant α-tocopherol on the mechanics and wear of UHMWPE was investigated. It is shown that the UHMWPE doped with α-tocopherol increases its crystallinity and hardness but decreases its gel content. Incorporation of α-tocopherol increases the elastic and plastic properties of the irradiated UHMWPE sample. Accelerated aging results in severely deterioration of the mechanical properties of irradiated UHMWPE samples. But the α-tocopherol doped UHMWPE sample shows good anti-oxidation property. Wear resistance of α-tocopherol doped irradiated UHMWPE sample was much better compared to the irradiated UHMWPE sample.